Green synthesis of nickle oxide nanoparticles for adsorption of dyes - Rashid, Israa Muzahem; Salman, Sami Dawod; Mohammed, Alaa Kareem; Mahdi, Yasmin Salih (Penerbit Universiti Kebangsaan Malaysia, 2022)
The green synthesis of nickel oxide nanoparticles (NiO-NP) was investigated using Ni(NO3)2 as a precursor, olive tree leaves as a reducing agent, and D-sorbitol as a capping agent. The structural, optical, and morphology of the synthesized NiO-NP have been characterized using ultraviolet–visible spectroscopy (UV-Vis), X-ray crystallography (XRD) pattern, Fourier transform infrared spectroscopy (FT-IR) and scanning electron microscope (SEM) analysis. The SEM analysis showed that the nanoparticles have a spherical shape and highly crystalline as well as highly agglomerated and appear as cluster of nanoparticles with a size range of (30 to 65 nm). The Scherrer relation has been used to estimate the crystallite size of NiO-NP which has been found about 42 nm. The NiO-NPs have subsequently used as adsorbents for adsorption of two types of dyes; methylene blue (MB) as cation dye and methyl orange (MO) as anion dye. The removal efficiency of dyes from contaminated water was investigated during various key parameters at room temperature; initial dye concentration (Co), pH, contact time (t), agitation speed, and adsorbent dosage. The maximum removal of MB dye was found to be 96% (Co=25 mg/l, pH=10, contact time=100 min, agitation speed=300 rpm and adsorbent dosage=6 g/l), while for MO the maximum removal reached 88% at (Co=20 mg/L, pH=2, t =160 min, agitation speed=300 rpm and adsorbent dosage=6 g/L). The experimental adsorption data were found to well obey Freundlich isotherm. The kinetic investigation showed that the adsorption process for both dyes followed a pseudo-second-order model with rate constants 0.0109 and 0.0079 (mg/g min) for MB and MO, respectively.